2005
DOI: 10.1007/s11243-004-3669-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of bis(2-aminophenyl)disulphide diimine derivatives and their ruthenium complexes

Abstract: Condensation of bis(2-aminophenyl)disulphide with aromatic aldehydes yielded the corresponding dithiophenyldiimines. Dinuclear ruthenium complexes were obtained by reacting the diimines (9) [bis(2-hydroxybenzaldehyde)-phenyldisulphide diimine], with RuCl 3 in the presence of L (L ¼ 2,2 0 -bipyridine, 1,10-phenanthroline, 3,4-diaminotoluene, pyridine and PPh 3 ) in EtOH. The two metal centres, connected through bridging chlorides, are in octahedral environments with one metal centre coordinated to sulphur and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 13 publications
3
21
0
Order By: Relevance
“…The mass spectrum of complex 2a, which was calculated by Finnigan's Excalibur Isotope Viewer showed the highest mass peak at 992.88 amu corresponding to a molecular formula of C 36 H 32 O 4 N 4 S 2 C l4 Ru 2 , which confirmed the binuclear nature of the metal complex. This indicated that one ruthenium atom is coordinated to an imine nitrogen, one terminal chlorine, one bipyridine and two bridging chlorine atoms, while the other ruthenium is coordinated to the other imine nitrogen, one terminal Cl, two bridging Cl and two water molecules, instead of a sulfur coordination as we reported earlier [8]. The positive mass spectrum gave major fragments at m/z 507 (sodium adduct of RuCl 2 (Bipy) 2 ) and 489 (C 23 H 19 N 3 OClRu) confirming the structure of 2a.…”
Section: Characterization Of Complexessupporting
confidence: 67%
See 2 more Smart Citations
“…The mass spectrum of complex 2a, which was calculated by Finnigan's Excalibur Isotope Viewer showed the highest mass peak at 992.88 amu corresponding to a molecular formula of C 36 H 32 O 4 N 4 S 2 C l4 Ru 2 , which confirmed the binuclear nature of the metal complex. This indicated that one ruthenium atom is coordinated to an imine nitrogen, one terminal chlorine, one bipyridine and two bridging chlorine atoms, while the other ruthenium is coordinated to the other imine nitrogen, one terminal Cl, two bridging Cl and two water molecules, instead of a sulfur coordination as we reported earlier [8]. The positive mass spectrum gave major fragments at m/z 507 (sodium adduct of RuCl 2 (Bipy) 2 ) and 489 (C 23 H 19 N 3 OClRu) confirming the structure of 2a.…”
Section: Characterization Of Complexessupporting
confidence: 67%
“…The reaction of RuCl 3 with 2-hydroxy benzaldehyde phenyldisulphide diimine, 2 in the presence of ligands L (L ¼ 2,2 0 -bipyridine, 1,10-phenanthroline or PPh 3 ) gave the binuclear complexes 2a-2c while with 2-chlorobenzaldehyde phenyldisulphide diimine, 3 or 2-nitrobenzaldehyde phenyldisulphide diimine, 4 in the presence of 1,10-phenanthroline or PPh 3 gave the binuclear complexes 3b, 3c and 4b [8]. We proposed earlier that in these complexes one of the ruthenium atoms is coordinated to one of the sulfur atoms as reported for similar types of complexes [6,7].…”
Section: Characterization Of Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the title compound was determined within a project on the synthesis of new ligands based on diaryldisulfides, see: Bhowon et al (2001Bhowon et al ( , 2005Bhowon et al ( , 2007; Raftery et al…”
Section: Related Literaturementioning
confidence: 99%
“…The microorganisms were clinical strains obtained from the Central laboratory, Victoria Hospital, Mauritius. Schiff bases 1-7 were synthesised by reacting bis(2-aminophenyl)disulfide with the corresponding aldehydes (Bhowon et al, 2005) while 8 and 9 by the reaction of vanillin and 2-aminophenol or 2-aminobenzoic acid (Uppiah et al, 2009).…”
Section: Methodsmentioning
confidence: 99%